Light in August [compact disc, unabridged] : the corrected text - Faulkner, William, 1897-1962 (Brilliance Audio, 2011)
Joe Christmas does not know whether he is black or white. Faulkner makes of Joe's tragedy a powerful indictment of racism; at the same time Joe's life is a study of the divided self and becomes a symbol of 20th century man. Light in August is the story of Lena Grove's search for the father of her unborn child, and features one of Faulkner's most memorable characters: Joe Christmas, a desperate drifter consumed by his mixed ancestry.